Pelatihan Peningkatan Usaha Pedagang Asongan Di Perumahan Buana Impian Kota Batam - Arif Rahman Hakim; Narti Eka Putria; Nurul Azwanti (Prosiding, 2023)
This activity aims to enhance the businesses of street vendors in Buana Impian Housing Complex 1 & 2, particularly those selling various goods. Initially, Buana 1 & 2 had a single RW 014, but in 2016, Buana Impian 2 became RW 028. Along the streets of Buana Impian Housing Complex 1 & 2, there are shops and a total of 53 street vendors. As part of this Community Service Program (PKM), the street vendors will receive training and guidance through lectures and discussions addressing the challenges faced by street vendors in Buana Impian Housing Complex 1 & 2. The educational and training materials will cover business management and entrepreneurship, accounting training for income and expenses, strategies for promoting businesses, and access to funding opportunities for street vendors. By participating in this training and education program, it is expected that the businesses of the street vendors will thrive and flourish.